2022
DOI: 10.1002/bab.2341
|View full text |Cite
|
Sign up to set email alerts
|

Dilute acid pretreatment for enhancing the enzymatic saccharification of agroresidues using a Botrytis ricini endoglucanase

Abstract: The enormous amount of agroindustrial residues generated in Brazil can be used as biomass to produce fermentable sugars. This study compared the pretreatments with different proportions of dilute acid. The method involved pretreatment with 0.5%, 1%, and 1.5% (v/v) sulfuric acid, followed by hydrolysis using the halotolerant and thermostable endoglucanase from Botrytis ricini URM 5627. The physicochemical characterization of plant biomass was performed using XRD, FTIR, and SEM. The pretreatment significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The decline of the enzymatic activity after 24 h may be due to alterations in physico-chemical conditions of medium, that is, pH, concentration of the substrate and absence of cofactors, saturation of active site, and an increased concentration of inhibitors. [52] Nevertheless, the particle size of the substrate, temperature, medium pH, inoculum size, aeration [53] cannot be ignored while considering optimum duration of an enzyme production. Guo et al reported that C:N ratio and pH were the most important factors that influenced the production of pectinase.…”
Section: Kinetics Of Pectinase Productionmentioning
confidence: 99%
“…The decline of the enzymatic activity after 24 h may be due to alterations in physico-chemical conditions of medium, that is, pH, concentration of the substrate and absence of cofactors, saturation of active site, and an increased concentration of inhibitors. [52] Nevertheless, the particle size of the substrate, temperature, medium pH, inoculum size, aeration [53] cannot be ignored while considering optimum duration of an enzyme production. Guo et al reported that C:N ratio and pH were the most important factors that influenced the production of pectinase.…”
Section: Kinetics Of Pectinase Productionmentioning
confidence: 99%
“…We further studied whether the crude enzyme solution of MtEG5-1 has an obvious ability to degrade corn straw. SEM can help to identify morphological changes in pretreated lignocellulosic materials [40]. SEM was used to compare the morphological changes in pretreated corn straw samples before and after catalysis by MtEG5-1.…”
Section: Scanning Electron Microscopy Of Hydrolyzed Corn Strawmentioning
confidence: 99%
“…Enzymes are used to degrade the lignocellulosic complex with the aim of breaking down the plant cell walls and promoting the release of carbohydrate monomers that can be fermented (Gupta et al 2016). Thus, recently, the search for e cient and resistant enzymes to produce fermentable sugars has intensi ed, especially for those produced by microorganisms (Silva et al 2021;Melanouri et al 2022;Silva et al 2022). The genus Penicillium contains more than 300 species of fungi (Massarente et al 2020;Caron et al 2021), of which the roqueforti species belongs to a group of 13 that are lamentous and one of the most studied species in the eld of biotechnology (El-shishtawy et al 2015; Kure and Skaar 2019; Dogan and Tekiner 2021).…”
Section: Introductionmentioning
confidence: 99%